Типологія категоріально-поняттєвого апарату феноменологічної соціології (Закінчення) - Шульга, О. (Социология: теория, методы, маркетинг, 2009)
The article is devoted to the theoretical problems of phenomenological sociology. The author analyses category-conceptual apparatus of P.L Berger and Th.Luckmann, as followers of A.Schutz. Their works are treated here as a “postclassical” period of phenomenological sociology, although both scientists don’t accept a possibility of “phenomenological sociology” and speak about phenomenology as a proto-sociology. The analysis is focused on the concept “legitimization” and other concepts which help to understand it, such as: “symbolic universe”, “externalization”, “objectivation”, “internalization”, “habitualization”, and “religious representations”. The author also compares Schutz’s context of the term “life-world” with that of Berger and Luck mann’s concept “world of everyday life”, that has narrower definition. An integral characteristic of their concept is “institutionalization”, they try to find mechanisms which make a life-world as taken-for-granted. To understand this fundamental process helps a conception of legitimization and symbolic universes. As a conclusion, an author makes an emphasis on the necessity of further development of theoretical level of phenomenological sociology. Some concepts of the theoretical systems of Peter L. Berger and Thomas Luckmann could be used for such an aim and have extremely high heuristic and gnoseological potential.